The Cybernetic Layer of Juri Lotman’s Metalanguage - Salupere, Silvi (Recherches sémiotiques / Semiotic Inquiry, 2015)
Most accounts of Juri Lotman’s legacy note his interest in information theory and cybernetics which is closely tied to his desire to use exact methods in the humanities. However, this connection itself has hardly been studied. This article focuses on a pair of terms with cybernetic origins found throughout Lotman’s works : “mechanism” and “ustrojstvo”. I try to show that these terms and the way they are used are not accidental but belong to an important strand in Lotman’s thought. An overview is presented of Lotman’s direct contacts with cybernetics and cyberneticians, and how the terms “ustrojstvo” and “mechanism” found their way into his metalanguage. The main focus is on exploring how Lotman understands this pair of terms. Translation problems related to them are also discussed.